Improved canola oil expeller extraction using a pilot-scale continuous flow microwave system for pre-treatment of seeds and flaked seeds. (November 2020) - Fouad M. Gaber, Mohamed A.; Knoerzer, Kai; Mansour, Maged Peter; Trujillo, Francisco J.; Juliano, Pablo; Shrestha, Pushkar
Abstract: Continuous flow microwave (MW) pre-treatment of canola seeds and flaked canola seeds increases the canola oil extraction yield on the expeller compared with conventional thermal pre-treatment using steam heating. Flaked seeds were "cooked" (heat-treated) with steam or using microwave heating in the temperature range of 70 °C–110 °C before expeller pressing. Microwave cooking at 100 °C resulted in the highest increase in the pressed oil yield which is an increase of 4.2% (w/w) on a pressed oil basis or 9.2% (oil in seed basis) compared with steam cooking. Whole canola seeds conditioning was conducted with microwaves or steam, in the temperature range of 40 °C–60 °C, followed by microwave or steam cooking at 100 °C to evaluate the effects on the expeller oil yield. The use of a continuous microwave process for combined conditioning of whole seeds at 50 °C and subsequent cooking of flaked seeds at 100 °C gave a 4.3% increase in expeller oil yield, compared with steam conditioning and cooking at the same temperature. The effects of steam and MW treatments on the dielectric properties of flaked seeds (dielectric constant, loss factor and loss tangent) were investigated at a microwave frequency of 2450 MHz at three temperatures (70, 90, and 100 °C). The results showed that the dielectric properties of MW treated flaked seeds were higher than those of samples treated with steam. The lipid classes of the extracted oil which included triacylglycerols (TAG), diacylglycerols (DAG), free fatty acids (FFA), and phospholipids (PL) and their fatty acid compositions from both the steam and continuous microwave processes were analysed. The contents of polyunsaturated fatty acids (PUFA), monounsaturated fatty acids (MUFA) and saturated fatty acids (SFA) after control and continuous MW cooking were not significantly different, nor was there any significant difference in the oil quality parameters such as FFA content, peroxide value (PV), phosphorus and chlorophyll contents between MW and conventional steam heating. Highlights: Pilot scale microwaves improved canola oil yield compared with steam treatment. The lipid classes of the extracted oil from a pilot scale and steam were identical. Dielectric properties of canola flaked seeds treated by MW describes structural change.